18F-FDG uptake and clearance in patients with compromised renal function. Issue 8 (August 2016) - Akers, Scott R.; Werner, Thomas J.; Rubello, Domenico; Alavi, Abass; Cheng, Gang
Abstract : Objective: The aim of this study is to evaluate whether compromised renal function has an effect on the uptake and clearance of 2-deoxy-2-[ 18 F]fluoro-D-glucose ( 18 F-FDG) in normal tissues on 18 F-FDG PET/CT imaging. Patients and methods: Patients were divided into three groups on the basis of their renal function status: 25 patients with normal renal function [estimated glomerular filtration rate (eGFR)>90 ml/min], 21 patients with mildly compromised renal function (90≥eGFR≥60 ml/min), and 12 patients with moderate or severe compromised renal function (eGFR<60 ml/min). All patients underwent 18 F-FDG PET/CT imaging at 1, 2, and 3 h after tracer injection. Maximum standardized uptake values (SUVmax ) were obtained in regions of interest for multiple tissue types. Results: Serial SUV values from 1 to 3 h were measured for different tissues including the aortic blood pool, liver, spleen, lung, lymph nodes, and skeletal muscles. The SUV values of 18 F-FDG uptake showed significantly decreased activity from 1 to 2 h as well as from 2 to 3 h for each tissue type, irrespective of renal function. There was no significant difference in SUVmean values between patients with normal and compromised renal functions, which was consistently observed for each tissue type and at each time point. In fact, the variance in individual SUV values within a group was more than the variance of SUV means between the groups with different renal functions for all tissue types and at 1-, 2-, or 3-h time points. Finally, the lack of dependence of SUV values in normal tissues on renal function is shown by very low r 2 values when comparing SUV and eGFR. Conclusion: Our data suggest that compromised renal function does not significantly compromise clearance of background activity of 18 F-FDG PET imaging. As a result, adjustment of 18 F-FDG dose or imaging time is not necessary in renal-impaired patients to achieve optimal imaging.